ANALISIS EFISIENSI PENGGUNAAN MODAL KERJA PADA CV. ALPAN TONDON PERKASA PERIODE 2016-2017 - Riza Eka Prastiwi; Jawoto Nusantoro; Ana Septiani (Jurnal Akuntansi AKTIVA, 2020)
Prastiwi, riza, eka. 2020. Analysis of the use of capital CV alpan tondon CV. The final task. The d3 accountingstudy program, the faculty of economics and business of metro university. An analysis that describes by calculating the ratio of existing ratios in the company using certain formulas. Theresults showed that the level of ratios for three years: (1) Liquidity ratios obtained Current Ratio results of138.2%, 111.7%, Quick Ratio of 130%, 102%. (2) Solvency Ratio results obtained from the Debt to Equity Ratioof 10.28x, 6.27x, Debt to Total Assets Ratio of 1.18x, 1.05x. (3) The financial condition based on the calculationof good ratios and the company's performance has increased every year.